Alteration of the gut microbiome in first-episode drug-naïve and chronic medicated schizophrenia correlate with regional brain volumes. (April 2020) - Ma, Xiaoqian; Asif, Huma; Dai, Lulin; He, Ying; Zheng, Wenxiao; Wang, Dong; Ren, Honghong; Tang, Jinsong; Li, Chunwang; Jin, Ke; Li, Zongchang; Chen, Xiaogang
Abstract: The human gut microbiome plays an important role in the basic neurodevelopmental processes of the central nervous system and has been implicated in several neuropsychiatric disorders. However, the connection between the gut microbiome and the underlying pathogenesis of schizophrenia (SCZ) is poorly defined. Here we analyzed the faecal samples from 40 first-episode drug-naïve SCZ (FSCZ) patients, 85 chronically antipsychotic-treated SCZ (TSCZ) patients and 69 healthy controls (HCs) using 16S rRNA gene sequence to determine whether the alterations of the gut microbiome were associated with SCZ or antipsychotic treatment. In addition, we acquired the T1-weighted brain imaging data by using structural magnetic resonance imaging to test whether microbial composition correlated with structural brain signatures. Our analyses revealed low microbiome alpha-diversity indexes in TSCZ patients but not in FSCZ patients as compared to HCs. Importantly, both FSCZ and TSCZ patients had distinct changes in gut microbial composition at certain taxa including Christensenellaceae, Enterobacteriaceae, Pasteurellaceae, Turicibacteraceae at the family level and Escherichia at genus level as compared to HCs. We also found significant disturbances of gut microbial composition in TSCZ versus FSCZ patients (eg. Enterococcaceae and Lactobacillaceae). Most interestingly, our exploratory analyses found specific SCZ-associated microbiota to be correlated with the right middle frontal gyrus (rMFG) volume which was aberrant in SCZ patients. Our findings extend prior work and suggest a possible link between the gut microbiome and brain structure which may be implicated in the pathology of SCZ. Highlights: Decreased microbiome alpha-diversity in TSCZ patients than FSCZ patients and healthy controls. Altered microbial composition was observed in both TSCZ and FSCZ patients. Certain SCZ-associated microbiota correlates with regional brain volumes.